Análise socioeconômica da Comunidade das Pitombeiras no interior da APA do Lagamar do Cauípe, Caucaia-Ce - Aguiar, Roberto de Paula (2013)
The Community of Pitombeiras, located in the municipality of Caucaia-CE is in a community of Traditional Fishermen, inserted within the Environmental Protection Area of the Lagamar Cauípe. Its surroundings involves precious environmental heritage, with the River Cauípe like an important natural resource for its main activity: fishing. Aiming to generate information that could serve as inputs to the process of implementation of effective measures for the shared management of Pitombeiras community, this study aimed at analyzing the socioeconomic status of the Pitombeiras community, relating to the environmental perception of actors as part of APA, understanding their stay in the area. Therefore, we performed a diagnostic social, economic and quality of life community and their respective impacts on socioeconomic relations of the community, and it was found as the community evaluates the implementation of the Port Pecém Industrial Complex near the APA. The results were obtained through comparison between: the foundations of literature, the study data, records and censuses, and field research. Thus, as the most significant results obtained by the study, it was identified that this community due to its current characteristics (where coexist customs, activities and traditional beliefs, habits and style of modern life), can be classified like "community neotradicional" yet still has among its members, several representatives of the natural region that would be classified as "traditional." It was observed that 75% of people living in the community of Pitombeiras for over fifteen years and that much of the population has no concept of living in an area of environmental protection. The level of education among community members is low and is reflected in employment and household income, as more than 50% of the economically active population is unemployed and about one-third of families have income below one minimum wage for a group average family of four. Many families believe that the implementation of the Industrial and Port Complex of Pecém nearby will help in generating employment and income, especially for young people. We observed a large deficiency as public services provided to the Community, which compromises the quality of life for residents and environmental quality of the APA's Lagamar Cauípe